Strategi implementasi proyek penguatan profil pelajar pancasila (p5) fase c di sekolah dasar - Yuniati Supriani; Siti Istiyati; Supianto Supianto (Didaktika Dwija Indria, 2025)
This research aims to: describe the strategy for implementation of the Strengthening Pancasila Student Profile Phase C Project at Ta'mirul Islam Elementary School Surakarta. This research uses a qualitative approach with a case study method. The subjects in this research were the VC class teacher, the P5 class V coordinator, and the VC class students. Data collection was carried out using interview techniques, observation and document analysis. The data validity testing technique used is triangulation of sources and techniques. Data analysis uses the Creswell model data analysis technique which consists of processing and preparing data for analysis, reading all the data, coding the data, connecting themes or descriptions, and making data interpretations. The results of this research are the P5 implementation strategies implemented in Phase C of SD Ta'mirul Islam Surakarta with the theme “Build the Body and Soul”, including project-based implementation strategies, habituation activity strategies, and integration strategies of local wisdom values. Through these strategies, we can strengthen the Pancasila Student Profile and achieve the dimensions of the Pancasila Student Profile, namely faith, devotion to God Almighty, and noble character, global diversity, mutual cooperation and creativity